2017
DOI: 10.1021/acscatal.7b00756
|View full text |Cite
|
Sign up to set email alerts
|

Domino C–H/N–H Allylations of Imidates by Cobalt Catalysis

Abstract: The domino C–H/N–H allylation of aryl imidates was accomplished by a versatile cobalt­(III) catalyst. In contrast to a tandem rhodium/palladium catalysis approach, an operationally simple cationic cobalt complex proved effective in the step-economical C–H/N–H functionalization of imidates to directly provide expedient access to decorated vinyl isoquinolines by kinetically relevant C–H activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
116
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(122 citation statements)
references
References 69 publications
4
116
0
2
Order By: Relevance
“…The catalytic properties of catalysts depend on their key parameters, such as crystallites size, structure and morphology [17]. Dispersion (and the average size) of the metallic active phase is one of the most important parameters characterizing the heterogeneous catalysts [8], which are essential for the activity, selectivity and stability of catalytic processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The catalytic properties of catalysts depend on their key parameters, such as crystallites size, structure and morphology [17]. Dispersion (and the average size) of the metallic active phase is one of the most important parameters characterizing the heterogeneous catalysts [8], which are essential for the activity, selectivity and stability of catalytic processes.…”
Section: Introductionmentioning
confidence: 99%
“…The crystallites size of metallic active phase are usually determined by hydrogen chemisorption, X-ray diffraction (XRD) or TEM (Transmission Electron Microscopy) [8,17,[20][21][22], but sometimes different results are found from various methods for the same catalyst. The differences in measurements of the crystallites size can result from methods limitation.…”
Section: Introductionmentioning
confidence: 99%
“…Lu and coworkers reported that for the Au@Pd core shell catalysts, the catalytic activities toward solvent-free aerobic oxidation of benzyl alcohol showed a volcanolike trend as a function of Pd shell thickness. 66 Small coverage of Pd adatoms on Au@Pd had a lower activity than continuous Pd shells. The turnover frequency (TOF) and specific activity gradually increased with Pd shell thickness, and reached maximums at 27 600 and 9800 h À1 on the Au@Pd core shell catalysts with 8 cycles Pd (shell thickness $0.8 nm).…”
Section: Substrate Surface Modification With Samsmentioning
confidence: 98%
“…66 In contrast, the Pd loadings increased considerably on an Au/SiO 2 catalyst with the number of Pd ALD cycles at the same deposition condition. Evidently, the Pd grew selectively on Au nanoparticles but not on the SiO 2 support and exclusively formed Au@Pd core shell structure.…”
Section: B Ald Temperature Reduction For Selective Growthmentioning
confidence: 98%
“…[43] Diese Art der Chemie wurde von anderen Forschern unter Verwendung verschiedener dirigierender Gruppen (DGs) zur Synthese allylischer Alkoholstrukturen weiterentwickelt (Schema 13;P rodukte 2-4). [47] Dieser Prozess beinhaltet die Bildung substituierter Dihydroisochi-noline mit lediglich CO 2 und H 2 Oa ls Nebenprodukten. Wegweisende Beiträge der Arbeitsgruppen von Ackermann und Glorius galten der Mn I -katalysierten C-H-Allylierung von Indolen mit entweder Pyridyl oder N-Pyrimidyl als dirigierende Gruppe (Schema 13;P rodukt 4).…”
Section: Allylierung Durch C-h-aktivierung Mit Vccsunclassified